The reality and dilemmas of higher education in IraqAnalytical vision in knowledge economies - سعدون, عبد الصمد; النداوي, خضير عباس (Journal of Economics and Administrative Sciences, 2011)
The subject of education, and since time immemorial, gripe the attention of the religious, intellectual, political, social and economic elites. This attention not only in Iraq, but in different countries in the world. There is a close correlation between the educational level of the societies and the edginess of its rising and advancement in all fields.In order to achieve the research objectives, the research has   been divided into three sections: section I include the historical, scientific, humanitarian evolution of education, starting from the first economic revolution (The Agricultural revolution) through the second economic revolution (The Industrial Revolution) and till the Third Economic revolution (Information Technology Revolution (IT). The second section dealt with: the reality of higher education in Iraq, and reviewed the experience in Iraq since the establishment of universities at the beginning of twentieth century until the present time.            The third section focused on: economic vision in light of contemporary information revolution in the world and its reflect on  higher education in Iraq, focusing on the intellectual property of students in various disciplines and their relevance to the practical use of information technology as an urgent priority in the higher education sector in Iraq. The answer came in a conclusion and recommendations for the development of higher education in Iraq.